Deep sequencing of pigeonpea sterility mosaic virus discloses five RNA segments related to emaraviruses - Elbeaino, Toufic; Digiaro, Michele; Uppala, Mangala; Sudini, Harikishan (Virus research, 2014)
•Five RNA segments of PPSMV were fully sequenced using deep-sequencing technology.•All RNA sequences of PPSMV showed high identity with orthologs of emaravirus species.•The phylogenetic trees constructed on single RNAs clustered PPSMV close to FMV and RRV emaraviruses.•PPSMV was proposed to be assigned to the genus Emaravirus. The sequences of five viral RNA segments of pigeonpea sterility mosaic virus (PPSMV), the agent of sterility mosaic disease (SMD) of pigeonpea (Cajanus cajan, Fabaceae), were determined using the deep sequencing technology. Each of the five RNAs encodes a single protein on the negative-sense strand with an open reading frame (ORF) of 6885, 1947, 927, 1086, and 1422nts, respectively. In order, from RNA1 to RNA5, these ORFs encode the RNA-dependent RNA polymerase (p1, 267.9kDa), a putative glycoprotein precursor (p2, 74.3kDa), a putative nucleocapsid protein (p3, 34.6kDa), a putative movement protein (p4, 40.8kDa), while p5 (55kDa) has an unknown function. All RNA segments of PPSMV showed the highest identity with orthologs of fig mosaic virus (FMV) and Rose rosette virus (RRV). In phylogenetic trees constructed with the amino acid sequences of p1, p2 and p3, PPSMV clustered consistently with other emaraviruses, close to clades comprising members of other genera of the family Bunyaviridae. Based on the molecular characteristics unveiled in this study and the morphological and epidemiological features similar to other emaraviruses, PPSMV seems to be the seventh species to join the list of emaraviruses known to date and accordingly, its classification in the genus Emaravirus seems now legitimate.